Determination of three ultraviolet filters in sunscreen formulations and from skin penetration studies by high-performance liquid chromatography - Fernanda Maria Pinto Vilela; Yris Maria Fonseca; Fabiana T. M. C. Vicentini; Maria José Vieira Fonseca; Maria da Penha Henriques do Amaral (Química Nova, 2011)
An analytical procedure to quantify 3-benzophenone, octylmethoxycinnamate and octylsalicylate was validated and employed to assess these ultraviolet filters in sunscreen formulations and from skin penetration studies. The effect of the vehicle on the skin retention of these filters was investigated. HPLC and extraction procedure were found to be reliable when obtaining data for the sunscreen formulations and for evaluation skin penetration. The results demonstrated that a cream gel generated higher epidermal concentrations of these filters than a lotion or cream-based formulation. Additionally, when comparing the skin retentions of each filter using the same formulation, 3-benzophenone showed the highest skin retention.